APPLICATION OF COMPUTER SYSTEMS ONTOLOGY IN THE PROCESS OF FUTURE ENGINEER AND EDUCATOR'S PRACTICAL ACTIVITY - Сергій Козіброда (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
This article develops the problem of the use of computer systems ontology in the professional activity of future engineers and teachers in the sphere of computer technology. The tasks of automated exchange of formal model descriptions as a main factor of a research performing in the sphere of ontology use have been grounded. The expediency of use of the ontology of computer systems in the following fields of intending engineers and teachers' training: artificial intelligence, interface, natural language processing, question-answer systems, classification of goods and services semantic mark-up of text, modelling organizational structure of enterprises, systems of reference information (NSI).